Ecological light transmiting concrete made from glass waste and acrylic sheets (2021)
In this research, recycling of 100% glass waste was evaluated for the manufacture of self-compacting mortars for applications in translucent building systems. The glass waste (WG) was ground and used as a fine aggregate in mortar mixtures with cement:WG proportion of 1:1.5, 1:1,75 and 1:2.0 with different water/cement (W/C) ratios. Properties such as fluidity, compressive strength, density, porosity, absorption, thermal properties, and characterization of the microstructure by SEM were analyzed. The results showed that as the WG content increases from 1:1.5 to 1:2.0 the compressive strength of the mortar decreases a maximum of 2.8% in samples with W/C:0.47, and this is due to the formation of microcracks and porosities, which cause the formation of a weakened and sparse interfacial zone which could be identified in the SEM tests. Nevertheless, the compressive strengths were between 20.6 MPa − 32.07 MPa, water absorption for mortars was between 12,92–14,74% and porosities from 23.02% to 25.93%. The thermal conductivity of the mortars was between 0.64 and 0.71 W/m.K. Additionally, the results of the spectrophotometry test for light transmission and the simulation in MATLAB allowed to obtain the brightness in the samples, it was possible to observe that the brightness varies according to the shape of the openings of the blocks, being the A design which allowed a greater passage of light (16%), and the materials developed could be classified as green building materials.